Synthesis of catalytic cobalt-containing coatings on alloy AL25 surface by plasma electrolytic oxidation - M. V. Ved'; A. V. Karakurkchi; N. D. Sakhnenko; A. S. Gorohivskiy (Хімія, фізика та технологія поверхні, 2017)
The study aims at the investigation of the influence of electrolyte composition and plasma electrolytic oxidation modes on the composition and morphology of a mixed aluminum and cobalt oxides at the AL25 alloy. Composition, morphology and surface roughness of the oxide systems are examined by scanning electron microscopy, X-ray analysis and atomic force microscopy. Mixed oxide coatings Al2O3·CoOx formed from the diphosphate electrolytes at various concentration ratio diphosphate / cobalt sulfate contain cobalt of 8–30at. % (in terms of metal) in the matrix of alumina. Plasma electrolytic oxidation in a two-stage mode of the incident power provided formation ofstrongly adhered coatings characterized by non-stoichiometry ratio of cobalt and oxygen as well as low content of silicon in deposits. Obtained mixed oxide systems have developed surface with alternating the spheroid and torus-shaped structures which is associated with a large number of catalytic sites. They exhibit catalytic behavior in the model reactions of CO conversion to CO2 and benzene oxidation not inferior to the contacts with noble metals. The coatings Al2O3·CoOx contribute to fuel economy and improve the environmental performance of the internal combustion engine thus can be recommended for use in the neutralization of gas emissions systems and as coatings for pistons of combustion chamber.